# How do you solve this difficult algebra problem?

##
F(x)= 2x^2-5x+3 and G(x)=1-4x-x^2

Calculate f(-2) + g(2)

F(x)= 2x^2-5x+3 and G(x)=1-4x-x^2

Calculate f(-2) + g(2)

##### 2 Answers

Aug 12, 2018

#### Explanation:

#"substitute "x=-2" into" f(x) " and "x=2" into "g(x)#

#f(-2)=2(-2)^2-5(-2)+3#

#color(white)(f-(2))=(2xx4)+(-5xx-2)+3#

#color(white)(f(-2))=8+10+3=21#

#g(2)=1-(4xx2)-(2)^2#

#color(white)(g(2))=1-8-4=-11#

#f(-2)+g(2)=21+(-11)=21-11=10#

#### Explanation:

The key realization is that

Plugging in

Plugging in

We have been asked to find

Hope this helps!